PENGARUH KESIAPAN UNTUK BERUBAH DAN PROACTIVE BEHAVIOR TERHADAP KINERJA - Kustini, Kustini; Izaak, Wilma Cordelia; Rini, Hesty Prima (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
This study aims to analyze the effect of readiness to change on employee performance through proactive behaviour. The readiness to change will lead to proactive behaviour in implementing the Financial Budget System (SIGARKU), which will impact employee performance. This study used the census sampling technique. The sample consisted of 80 lecturers and education staff of UPN